Evaluation of Blood Pressure in Children Treated with Ceftriaxone: A Case-Control Study - Esmaeili, Mahdi; Sarmadian, Roham; Fatahibayat, Gholamali; Yousefichaijan, Parsa; Habibi, Danial (Jordan Journal of Pharmaceutical Sciences, 2023)
Background: In children, high blood pressure can develop into hypertension and its consequences during puberty and adulthood. High blood pressure in children is often secondary to other causes, including renal diseases. Nephrolithiasis is one of the causes of secondary hypertension. The extensive use of cephalosporins in hospitals, particularly ceftriaxone, can result in nephrolithiasis. Therefore, the purpose of this study was to assess the relationship between ceftriaxone treatment and elevated blood pressure in children. Method: The research was conducted as a case-control study over an 18-month period from 2018 to 2019. In this study, blood pressure was measured in 111 children aged 3-13 years who were hospitalized at Amir Kabir Hospital in Arak and received ceftriaxone for at least 48 hours. As a control group, 111 children who did not receive ceftriaxone had their blood pressure measured. The blood pressure levels and percentiles of children in the two groups were then compared. Result: In the case and control groups, the mean age was 5.1±1.61 and 6.04±2.4 years, and the mean height was 109.17±10.71 and 114.86±12.95 cm, respectively. A slightly higher mean systolic blood pressure percentile was observed in the case group (65.59±18.17) than in the control group (65.28±14.51) (P=0.112), and the mean diastolic blood pressure percentile was also slightly higher in the case group (58.89±18.88) than in the control group (54.85±19.28) (P=0.317). The difference in diastolic blood pressure was greater than in systolic blood pressure. However, these detected differences were slight and not statistically significant. Conclusion: This study showed no association between blood pressure levels and ceftriaxone treatment in children older than three years who received the medicine for at least 48 hours. However, additional research is suggested, focusing on the effects of the medicine at higher doses and over a longer period of time following administration.